Histomorphological investigation of tongue of Porcupine Hystrix cristate - Kadhim, Abdularazzaq Baqer (The Iraqi Journal of Veterinary Medicine, 2018)
Anatomical and histological explorations of the tongue in ten adult male Porcupine (Hystrix cristata) collected from AL-Diwanyha city by the hunter, after porcupine prepared the tongue illustrious after that the position, shape dimensions were enrolled. The square-shape of body, thicken less steadily toward caudal part of tongue. Root was tends caudally in the direction of the epiglottis. Torus linguae found on the caudal part of the dorsal surface of the tongue. In the end of lateral surface of tongue have foliate papilla osculate the premolar teeth. The length, apex, body and root of the tongue were (7.6±0.66, 1.25±0.23, 4.95±0.2, and 1.4±0.26 cm), respectively. The width, apex, body, and root of the tongue were (1.80±0.77, 0.35±0.49, 1±0.22 and 0.45±0.14, respectively. In the dorsal and lateral surface have muscle fibers from skeletal type and loose connective tissue bounded by keratinized stratified squamous epithelium while in the ventral lingual surface were non-keratinized. In the dorsal surface of body there were filiform papillae, but less at the lateral surface of the body. While the shape of circumvallate papillae was similar to furrow, and there was taste buds on the both dorsal and lateral sides of the tongue. Fungiform papillae had wide curved keratinized surface, with taste buds on the dorsal surface. Lamina propria and submucosa was loose connective tissue with more of collagen fiber.